Forest Research in the German Democratic Republic - Buggel, Henry (Indian Forester, 1967)
In the German Democratic Republic forest research work is done at the German Academy of Agricultural Sciences (Forestry Section) and at the Faculty of Forestry as part of the Technical University of Dresden. Present substance and form of the research work differs extraordinarily from forest research work in early years. The traditional research work had two main faults: It needed a too long time carrying over the research results into practice, and research work was not co-ordinated and therefore double work, waste, hobby research, etc., were inevitable. One of the most important research task is the long-Term, large-scale planning ahead of the national economy until 1980. That means finding out possibilities for increasing the production of round wood qualitatively and quantitatively by lowest prime costs, to reduce considerably the import of wood. In this connection it must also be considered the socio-logical research forestry and many forest economical problems in German Democratic Republics State Forest Enterprises. All proposed new research projects are deliberated by the Academy Council, which has to audit and to test for necessity, economical imporantance for the republic and forestry. The results of the research work being presented in a research report must be defended before a body of concerned scientists and experts in forestry. One-man research is seldom profitable, and therefore team work is becoming desirable. Many socialist research teams stand mutually in socialist competition and emulate best results by lowest expense in time and money.